2014
DOI: 10.1002/jctb.4386
|View full text |Cite
|
Sign up to set email alerts
|

Removal of non‐steroidal anti‐inflammatory drugs from primary and secondary effluents in a photocatalytic membrane reactor

Abstract: BACKGROUND: The pollution of the aquatic environment by pharmaceuticals has become a serious problem. Conventional technologies applied in water or sewage treatment plants are not effective in drugs removal, therefore there is an urgent need to develop new methods. RESULTS:The removal of diclofenac (DCF), ibuprofen (IBU) and naproxen (NAP) sodium salts in a photocatalytic membrane reactor (PMR) utilizing direct contact membrane distillation and UV-C radiation from ultrapure water, tap water, primary effluents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 37 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…Better mineralization in secondary than primary effluent [243] Although PMs have been studied for removal of some organics like humic acids [195,210], textile dyes [211,223,229,244,245], and bacterial disinfection [196], only few studies are available on use of this technique for remediation of PhACs. In fact, the most relevant study on removal of PhACs by PMs was recently reported by Ramasundaram et al [45].…”
Section: Hybrid/one Pot Process -Photocatalytic Membranes/reactors (Pmentioning
confidence: 99%
“…Better mineralization in secondary than primary effluent [243] Although PMs have been studied for removal of some organics like humic acids [195,210], textile dyes [211,223,229,244,245], and bacterial disinfection [196], only few studies are available on use of this technique for remediation of PhACs. In fact, the most relevant study on removal of PhACs by PMs was recently reported by Ramasundaram et al [45].…”
Section: Hybrid/one Pot Process -Photocatalytic Membranes/reactors (Pmentioning
confidence: 99%
“…Meanwhile, the non-volatile components stay in the feed side of the membrane and their theoretical retention rate is 100%. The temperature and the composition of the solution in the layers adjacent to the membrane determine the vapor pressure difference between both sides of membrane, which acts as the driving force of the mass transfer through the membrane [82,83]. There are several types of MD configurations such as direct contact MD (DCMD), vacuum MD, sweep gas MD and air gap MD.…”
Section: Coupling Photocatalysis With Membrane Distillationmentioning
confidence: 99%
“…In a photocatalysis-DCMD system, the photocatalyst cannot be evaporated into gas phase, thus it is unable to pass through the membrane pores and the membrane fouling caused by photocatalyst particles reduces consequently. Despite the advantages, a disadvantage of PMR-DCMD is that the permeate flux is relative lower compared to that in the pressure-driven processes [82]. …”
Section: Coupling Photocatalysis With Membrane Distillationmentioning
confidence: 99%
“…Photocatalytic materials have attracted great interest due to their ability to utilize light energy to alleviate the deterioration of water resources. [18][19][20][21] Titanium dioxide (TiO 2 ), an excellent photocatalyst which is non-toxic, cheap, and chemically stable, is hailed as one of the most promising candidate for organic pollutant degradation. [22][23][24][25] Incorporation of TiO 2 into filtration membrane enhances its flux and hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%